UZBEK LANGUAGE LOCALIZED UNITS (CAHIERS MAGELLANES-NS, 2024)
ABSTRACT: This article describes the Uzbek language as a whole and locality, the relationship of localization, localized units formed by the relationship of interrelated and mutually demanding elements. In world linguistics, the term "communicative field" was also created as part of the concepts related to the field, in which the communicative act, the discussion of the discourse through certain syntagmatic connections, is recognized as a field.